Is SARS-CoV-2 the only cause of long-COVID? - Pintos, Ilduara; Moreno-Torres, Víctor; Ibánez-Estéllez, Fatima; Corrales-Rodriguez, Pilar; Treviño, Ana; Corpas, Manuel; Corral, Octavio Jorge; Soriano, Vicente; de Mendoza, Carmen (AIDS Reviews, 2023)
Around 10% of adults infected with SARS-CoV-2 that survive a first episode of COVID-19 appear to experience long-term clinical manifestations. The signs and symptoms of this post-acute COVID-19 syndrome (PACS) include fatigue, dyspnea, joint pain, myalgia, chest pain, cough, anosmia, dysgeusia, headache, depression, anxiety, memory loss, concentration difficulties, and insomnia. These sequelae remind the constellation of clinical manifestations previously recognized as myalgic encephalomyelitis (ME) or chronic fatigue syndrome (CFS). This condition has been described following distinct infectious events, mostly acute viral illnesses. In this way, the pathophysiology of PACS might overlap with mechanisms involved in other post-infectious fatigue syndromes. The risk of PACS is more frequent in women than men. Additional host genetic factors could be involved. There is a dysregulation of multiple body organs and systems, involving the immune system, the coagulation cascade, endocrine organs, autonomic nervous system, microbiota–gut–brain axis, hypotha-lamic–pituitary–adrenal axis, hypothalamic–pituitary–thyroid axis, etc. Hypothetically, an abnormal response to certain infectious agents could trigger the development of post-infectious fatigue syndromes.
Keywords: chronic fatigue syndrome; COVID-19; long-COVID; myalgic encephalomyelitis; persistent COVID; post-acute COVID-19 syndrome; post-infectious fatigue syndrome; post-viral fatigue; SARS-CoV-2; Scopus; JCR